2012
DOI: 10.1021/jf303658m
|View full text |Cite
|
Sign up to set email alerts
|

Double Schiff Base Adducts of 2,3-Butanedione with Glycine: Formation of Pyrazine Rings with the Participation of Amino Acid Carbon Atoms

Abstract: The 1,2-dicarbonyl compounds are well-known for their ability to undergo a one-to-one interaction with amino acids and generate aroma-active pyrazines through the Strecker reaction. An earlier publication reported the generation of tetrahydropyrazine moiety from the double addition of amino acids to 1,2-dicarbonyl compounds. To evaluate the potential of this intermediate to undergo oxidation and form pyrazines, a model system composed of glycine and 2,3-butanedione was evaluated under pyrolytic conditions at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…While BA can react with glycine to form tetramethylpyrazine, its reaction with AS does not favorably produce a species able to reduce the imine-substituted BA (m/z 86) needed for pyrazine formation. 63 Light Absorbance. The reacted BA + AS system exhibits light absorbance similar to that of other small carbonyls, 44 with absorbance peaks at approximately 190, 224, and 280 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While BA can react with glycine to form tetramethylpyrazine, its reaction with AS does not favorably produce a species able to reduce the imine-substituted BA (m/z 86) needed for pyrazine formation. 63 Light Absorbance. The reacted BA + AS system exhibits light absorbance similar to that of other small carbonyls, 44 with absorbance peaks at approximately 190, 224, and 280 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The presence of the α-diketone in BA leads to a decreased number of imidazole derivatives and an increased presence of oxazole derivatives compared to other carbonyl + AS systems. , Additionally, no pyrazines were identified in the BA + AS system. While BA can react with glycine to form tetramethylpyrazine, its reaction with AS does not favorably produce a species able to reduce the imine-substituted BA ( m / z 86) needed for pyrazine formation …”
Section: Resultsmentioning
confidence: 99%
“…Their formation most probably occurred from amino acids and vicinal diketones. A recent publication has reported the unexpected formation of 2,3‐dimethylpyrazine and 2,3,5‐trimethylpyrazine in addition to the expected tetramethylpyrazine in a model system composed of glycine and 2,3‐butanedione . Furans are derivatives of furan and can be found in heat‐treated commercial foods formed by thermal degradation of natural food constituents .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yaylayan has also shown that under some conditions, part of the glycine carbon skeleton can be found in the pyrazine ring (Guerra and Yaylayan, 2012 dicarbonyl/amino acid soup, there are many permutations and combinations of carbonyl-amine condensations that can lead to the formation of pyrroles and pyrazines. For example, the dicarbonyls, rather than undergoing a Strecker degradation, can form a double Schiff base with glycine that can cyclise leaving two glycine-based carbons in the pyrazine ring.…”
Section: Formation Of Pyrazinesmentioning
confidence: 99%